International tourist satisfaction in Malaysia: antecedents and consequences. Issue 3 (3rd July 2018) - Yap, Ching Seng; Ahmad, Rizal; Zhu, Pengfei
ABSTRACT: This study examined two antecedents – perceived value and destination image, which affect international tourist satisfaction from visiting Malaysia, and two consequences of tourist satisfaction – tourist loyalty and complaining behaviour. Data were collected using a questionnaire survey from 317 departing international tourists at two international airports in Kuala Lumpur. Results indicated that perceived value and destination image related positively with tourist satisfaction which in turn, lead to tourist loyalty. However, tourist dissatisfaction did not lead to complaining behaviour, and complaining behaviour did not have any significant relationship with tourist loyalty. The study provided insights for tourism practitioners on the behaviours of international tourists for the purpose of promoting Malaysia as a tourism destination.